Permeation behavior of low-melting-point Sn–Bi alloy in the fiber channel of pine wood. (November 2020) - Wang, Zhong-Liang; Wang, Min; Li, Lan-Xin; Bao, Yan-Ping
Abstract: Wood and metal are the two most common materials, both with distinct advantages and disadvantages. Through the metallization process, the inherent defects of the two materials can be avoided, so that the composite material exhibits excellent structural properties and anisotropy. In this study, the pine wood was pretreated with dilute ammonia (5%), and then the low melting point Sn–Bi alloy was filled into the pine fiber without lignin at 180 °C and 3000 Pa. The density of metallic wood is about 3 times that of pine, while the impact toughness can be up to 2 times that of pine. By building the capillary buddle model, the filling mechanism of molten metal in pine wood was analyzed, and it was clear that high vacuum, high temperature, large porosity and large tracheid diameter are the conditions for rapid penetration. The conductive anisotropy was found on metalized wood, making metalized wood available in different places with requirements for electromagnetic shielding and antistatic. Graphical abstract: Unlabelled Image Highlights: Ammonia treatment can play a role in modifying pine fiber. The capillary bundle theory is innovatively applied to the metallized wood. The infiltration effect is determined by porosity, fiber diameter, temperature and vacuum. Metallic wood has excellent conductivity anisotropy.